Diagnostic accuracy of sliding sign for detecting pouch of Douglas obliteration and bowel involvement in women with suspected endometriosis: systematic review and meta‐analysis. (12th September 2022) - Alcázar, J. L.; Eguez, P. M.; Forcada, P.; Ternero, E.; Martínez, C.; Pascual, M. Á.; Guerriero, S.
ABSTRACT: Objective: The aim of this systematic review and meta‐analysis was to evaluate the diagnostic accuracy of the sliding sign on transvaginal ultrasound (TVS) in detecting pouch of Douglas obliteration and bowel involvement in patients with suspected endometriosis, using laparoscopy as the reference standard. Methods: A search for studies evaluating the role of the sliding sign in the assessment of pouch of Douglas obliteration and/or bowel involvement using laparoscopy as the reference standard published from January 2000 to October 2021 was performed in PubMed/MEDLINE, Web of Science, CINAHL, The Cochrane Library, ClinicalTrials.gov and SCOPUS databases. The Quality Assessment of Diagnostic Accuracy Studies‐2 (QUADAS‐2) was used to evaluate the quality of the studies. Analyses were performed using MIDAS and METANDI commands in STATA. Results: A total of 334 citations were identified. Eight studies were included in the analysis, resulting in 938 and 963 patients available for analysis of the diagnostic accuracy of the sliding sign for pouch of Douglas obliteration and bowel involvement, respectively. The mean prevalence of pouch of Douglas obliteration was 37% and the mean prevalence of bowel involvement was 23%. The pooled estimated sensitivity, specificity, positive likelihood ratio, negative likelihood ratio and diagnostic odds ratio of the sliding sign on TVS for detecting pouch of Douglas obliteration were 88% (95% CI, 81–93%), 94% (95% CI, 91–96%), 15.3 (95% CI, 10.2–22.9), 0.12 (95% CI, 0.07–0.21) and 123 (95% CI, 62–244), respectively. The heterogeneity was moderate for sensitivity and low for specificity for detecting pouch of Douglas obliteration. The pooled estimated sensitivity, specificity, positive likelihood ratio, negative likelihood ratio and diagnostic odds ratio of the sliding sign on TVS for detecting bowel involvement were 81% (95% CI, 64–91%), 95% (95% CI, 91–97%), 16.0 (95% CI, 9.0–28.6), 0.20 (95% CI, 0.10–0.40) and 81 (95% CI, 34–191), respectively. The heterogeneity for the meta‐analysis of diagnostic accuracy for bowel involvement was high. Conclusion: The sliding sign on TVS has good diagnostic performance for predicting pouch of Douglas obliteration and bowel involvement in women with suspected endometriosis. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.